EVALUASI PENGGUNAAN OBAT ASAM URAT DAN POLA PERESEPANNYA PADA PASIEN GOUT ARTRITIS DI INSTALASI RAWAT INAP DI RSUD DELI SERDANG LUBUK PAKAM TAHUN 2020 - Rahayu, Asvia; Anna Teresia Marbun, Romauli; Nopita Sari Manalu, Dian; Siregar, Sa’adah; Ade Rizky, Vincentia; Krisdianilo, Visensius (Jurnal FARMASIMED (JFM), 2021)
Uric acid is a disease that arises due to excess purine in the body caused by uric crystals in the joint tissue that attacks the fingers, elbows, knees, toes, toes and heels. Gouty arthritis is a progressive disease caused by deposition of monosodium urate crystals (MSU) found in the joints, kidneys, and other connective tissue due to chronic hyperuricemia. The incidence of gouty arthritis is common in men as many as 25 patients (65.8%) and women as many as 13 patients (34.2%). The incidence of gouty arthritis continues to increase with age, at the age of 21-35 years (7.9%), ages 36-55 years (36.7%), age 56-65 years (28.9%), and at the age of 66 -75 years (26.3%). The purpose of this study was to examine the use of uric acid and its prescription patterns in arthritis patients in Deli Serdang Lubuk Pakam Hospital in 2020 in terms of the right parameters according to the indications, the right patients, the right drugs, and the right dosages. This research is a non-experimental study, data retrospective retrieval was done by looking at the medical record data of arthritis gout patients and analyzed descriptively. Sampling as many as 38 patients with puposive sampling method. Inclusion criteria in this study were patients who were diagnosed with gout and given arthritis medication with complete medical record data. The results of the study evaluated the use of gout and its prescribing patterns in 38 patients at Deli Serdang Lubuk Pakam Regional Hospital in 2020, which were 100% correct, 100% right, 100% right, and 96% right.